Clostridium Scindens Protects Against Vancomycin‐Induced Cholestasis and Liver Fibrosis by Activating Intestinal FXR‐FGF15/19 Signaling - Jintao Xiao; Yanliang Hou; Xingyang Luo; Yuhao Zhu; Wenhu Li; Bingbing Li; LinXiang Zhou; Xia Chen; Ying Guo; Xiaomei Zhang; Haiyue He; Xiaowei Liu (Advanced Science)
Abstract Primary sclerosing cholangitis (PSC) is characterized by abnormal bile acid metabolites and altered gut microbiota, with no effective treatments available. Vancomycin, a glycopeptide antibiotic, has emerged as a promising candidate. However, the mechanism by which vancomycin impacts the progression of PSC remains unknown. Mice treated with vancomycin exhibit increased hepatic collagen deposition and injury, due to the inhibition of intestinal FXR‐FGF15/19 axis and the elevation of bile acid levels. These effects are associated with the reduction in Clostridia XIVa, especially Clostridium scindens (C. scindens). Gavage of C. scindens alleviates vancomycin‐induced bile acid accumulation and liver fibrosis via activating intestinal FXR‐FGF15/19 signaling. Similar effects are observed in mice treated with engineered Escherichia coli Nissle 1917 that are capable of expressing bile acid 7α‐dehydratas (BaiE) from C. scindens (EcN‐BaiE). Activating intestinal FXR‐FGF15/19 signaling by fexaramine (Fex) or recombinant protein FGF19 reverse vancomycin‐induced liver injury and fibrosis. These results demonstrate that long‐term oral vancomycin exacerbates cholestatic liver injury, while C. scindens mitigates this effect by activating the intestinal FXR‐FGF15/19 signaling pathway. This underscores the importance of monitoring bile acid levels in PSC patients receiving vancomycin treatment and suggests that C. scindens may serve as a potential therapeutic approach for PSC patients.